(untitled) (International Seven Journal of Health Research, 2024)
Acute appendicitis is the main cause of non-obstetric surgery in pregnant women. In the past, the main approach was to seek as little intervention as possible, at least until a more advanced gestational age was reached. However, recent studies show that early intervention has several benefits for both the mother and the fetus. Today, it is understood that regardless of the trimester of pregnancy, diagnosis and treatment need to be carried out as soon as possible in order to avoid future complications. The main therapeutic method is laparoscopic appendectomy. This literature review seeks to bring together the main findings in recent years on the positive and negative aspects of laparoscopic appendectomy in pregnant women, in order to understand whether it is in fact the best method currently available for this type of situation.